PENGAWASAN CAMAT TERHADAP PEMBANGUNAN DESA TERTINGGAL DESA ULAK PATIAN KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU TAHUN 2012 - Taufiq "; M. Y. Tiyas TInov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study, entitled Supervision Camats Against Disadvantaged Rural DevelopmentRural District of Fullness Ulak Patian Rokan Hulu in 2012. Research is motivated by RokanHulu Regency Regulation No. 39 Year 2011 on the transfer of part of the authority to theregent Rokan Hulu District Head for performance of Local Government, which where camatdituntuk participate actively in monitoring the development of the village, sub-district andvillage as required in order to run in running the village administration tasks,synchronization between the village and district governments can influence the motion of thegrowth of rural development.Problems in this sekripsi that control sub-districts, rural development tertinggalanPatian Ulak village and village government administrative services. For this study aims todetermine how the monitoring of the progress of the village sub-district head, the constraintsin rural villages as well as the supervision of village administrative services. The methodused in this study is a qualitative method that describes the data descriptively. Datacollection techniques used were dokumentasidan field study by interviewing while the sourcedata used is primary data collected from the study site and supported by secondary data.From the research conducted hasi, camat supervision in rural development is notmaximized, it is influenced by several factors, namely: its lack of synchronization between thevillage government districts, villages lack proper policies, as well as the physical condition ofthe road is inadequate. However, the village government to do some role to support theeconomic growth of the community one of which is to improve the quality of education.Keywords: Delegation of authority, development, underdeveloped villages.